A Delphi Consensus on Patient Reported Outcomes for Registries and Trials Including Patients with Intermittent Claudication: Recommendations and Reporting Standard. (November 2022) - Arndt, Helene; Nordanstig, Joakim; Bertges, Daniel J.; Budtz-Lilly, Jacob; Venermo, Maarit; Espada, Cristina Lopez; Sigvant, Birgitta; Behrendt, Christian-Alexander
Abstract : Objective: This study aimed to develop a core set of patient reported outcome quality indicators (QIs) for the treatment of patients with intermittent claudication (IC), that allow a broad international implementation across different vascular registries and within trials. Methods: A rigorous modified two stage Delphi technique was used to promote consensus building on patient reported outcome QIs among an expert panel consisting of international vascular specialists, patient representatives, and registry members of the VASCUNET and the International Consortium of Vascular Registries. Potential QIs identified through an extensive literature search or additionally proposed by the panel were validated by the experts in a preliminary survey and included for evaluation. Consensus was reached if ≥ 80% of participants agreed that an item was both clinically relevant and practical. Results: Participation rates in two Delphi rounds were 66% (31 participants of 47 invited) and 90% (54 of 60), respectively. Initially, 145 patient reported outcome QIs were documented. Following the two Delphi rounds, 18 quality indicators remained, all of which reached consensus regarding clinical relevance. The VascuQoL questionnaire (VascuQoL-6), currently the most common patient reported outcome measurement (PROM) used within vascular registries, includes a total of six items. Five of these six items also matched with high rated indicators identified in the Delphi study. Consequently, the panel recommends the use of the VascuQoL-6 survey as a preferred core PROM QI set as well as an optional extension of 12 additional patient reported QIs that were also identified in this study. Conclusion: The current recommendation based on the Delphi consensus building approach, strengthens the international harmonisation of registry data collection in relation to patient reported outcome quality. Continuous and standardised quality assurance will ensure that registry data may be used for future quality benchmarking studies and, ultimately, positively impact the overall quality of care provided to patients with peripheral arterial occlusive disease.